ХАЛЫҚТЫҢ ТӘБИЙИЙ ҲӘРЕКЕТИНЕ ИЛИМИЙ КӨЗҚАРАС - Утепова, Г.Б. (FAN va JAMIYAT, 2024)
This article talks about the natural regeneration of the population, specific indicators of birth and death in the countries of the world, the reproductive desire of the population, endogenous and exogenous factors of death, gross coefficient and net coefficient, as well as the average life expectancy of the population.